Studies of Used to Forest Product by Dayak Meratus Tribe in the Forest Area of Meratus Mountain, Hulu Sungai Tengah Regency - Sunarhadi, M. Amin; Kartikawati, Siti Masitoh (Universitas Muhammadiyah Surakarta, 2005)
Dayak Meratus tribe is the native tribe that lives in the forest area of Meratus Mountain. Biological basic data on plant biodiversity in the area, particularly plants utilized by Dayak Meratus tribe, have not been much discovered. The research are: (1) to discover the traditional characteristic and knowledge of Dayak Meratus tribe, (2) to determine the priority of plants to be conserved, (3) to study local government policy in the forest resources management and, (4) to determine the strategy of priority plants conservation. Research was conducted at Meratus Mountain forest area, Hulu Sungai Tengah Regency and Herbarium Bogoriense, Biological Research and Development Center of LIPI, Bogor, from July to September 2002. Determination of priority plants is based on 4 criteria: (1) Index of Cultural Significance that consists of three value, that are: quality of use, intensity of use, exclusivity of use, (2) Distribution, (3) Status in the nature area (wild, semi domesticated, domesticated/cultivated), and (4) the characteristic of use/utilization by the community (commercial, subsistence). The number of plant species used by Dayak Meratus Tribe is 240 species of 18 use characteristic, 2 species endemic, 14 species rare, 111 species have more than one utilization function, 20 medicinal plants can be used as a consideration in changing the status of protected forest to conservation areas with status of national park.